From Phase Change Materials to Green Solvents: Hydrophobic Low Viscous Fatty Acid-Based Deep Eutectic Solvents - Florindo, Catarina (2018)
Inspired by the use of fatty acids in development of low temperature latent heat storage materials, novel low viscous and hydrophobic deep eutectic solvents (DESs) based exclusively on fatty acids are herein proposed as sustainable solvents. Three DESs were prepared by exclusively combining fatty acids, namely octanoic acid (C8), nonanoic acid (C9), decanoic acid (C10), and dodecanoic acid (C12), which can simultaneously act as hydrogen bond donors and acceptors. The obtained fatty acid-based DESs were analyzed in order to check their structures, purities, and proportions. Water stability was also carefully evaluated through 1H NMR. Fatty-acid DESs melting point diagrams were determined by visual observation. Good agreement was obtained between the experimental eutectic point and that predicted by considering an ideal system of two individually melting compounds. Important solvent thermophysical properties, such as density and viscosity of the dried and water-saturated DESs, were measured. Finally, the removal of bisphenol A, a persistent micropollutant present in aqueous environments illustrates the potential of binary and ternary fatty acid-based DESs as extraction solvents. All prepared DESs showed good ability to extract bisphenol A from water with extraction efficiencies up to 92%.